Analisis Yuridis Perjanjian Co-Branding Gas Teknologi Map Antara Pt.Rinder Energia Consulting dengan PT. Pertamina Indonesia - Purba, Ardiansyah Purba; Leviza, Jelly; Siregar, Taufik (Universitas Medan Area, 2020)
Along the development of the era of PT Pertamina it is deemed necessary to have business partners, especially oil and gas consultant company, PT Rinder Energia. It is expected that this business partner will have a positive impact for both parties, especially PT Pertamina as BUMN. One of the products that will be agreed by both parties is map map. This map map is a cutting-edge tool that will help PT Pertamina in exploring and producing better oil and gas. The formulation of the issues to be raised is how the rights and obligations of the parties in the contract of sale and purchase map map between PT Rinder Energia with PT Pertamina, whether the contract of sale and purchase map map is in accordance with the principles of contract law in Indonesia and how the form of dispute settlement In a contract between PT Rinder Energia and PT Pertamina Indonesia. The purpose and benefit of this research is to know the form of rights and obligations of the parties in the contract of sale and purchase map map between PT Rinder Energia with PT Pertamina. To find out the form of dispute settlement in contract between PT Rinder Energia and PT Pertamina Indonesia. The results of this study may be additional refrentions for students, lecturers, or readers interested in Civil Law, in particular Contract Law. This type of research is normative juridical that describes the review and explain and analyze normative provisions associated with the contents of the contract or agreement between PT. Rinder Energia with PT. Pertamina Indonesia in buying and selling map map. The research undertaken aims to examine the rules contained in a contract that has been agreed upon by both parties in accordance with applicable legislation. The implementation of the sale and purchase agreement in the form of a map between PT.RINDER ENERGIA and PT.PERTAMINA is basically an agreement born from the principle of freedom of contract. If one party makes a sale in the form of a map between PT.Rinder Energia and PT.Pertamina Indonesia then the dispute must be submitted to the arbitration tribunal in accordance with the provisions of BANI.